DEFINITION OF TOLERANCE IN THE PARAMETERS ELECTRONIC SYSTEMS ACCOUNT OF INTERFERENCE - E. G. Unichenko (Научный вестник МГТУ ГА, 2016)
In the article the possibility of accounting for changes in the parameters of the equivalent electronic systems under the influence of an additive mixture useful signal and interference by determining the required tolerances of parameters for different disturbance situations. The proposed approach allows us to assess the interference immunity of analog communication systems of different types of modulation.